Maximizing Utilization of Energy from Crop By-products - Budi Haryanto (Indonesian Center for Animal Research and Development, 2014)
The availability of crop by-products is huge during harvesting times as related to the vast agricultural land area; however, their utilization is still limited due to lack of knowledge and handling problem. Seasonal effect is obvious especially during wet season when high rainfall hinders proper management of crop by-products. Crop by-products are energy rich feedstuffs in the form of chemical substance such as cellulose and hemicellulose. The utilization of cellulose and hemicellulose as sources of energy can be maximized by the application of technologies to increase the digestibility. Cellulose is polymer of glucose while hemicellulose is polymer of xylose which both can be converted to volatile fatty acids by rumen microbial enzyme activities and subsequently used by the host animal as source of energy. In addition, cellulose and hemicellulose can also be used as substrates for bioethanol production leaving behind residual matter with higher concentration of protein which is also appropriate for ruminant feeds. The fat content of crop by-products such as those in rice bran and corn germ can be extracted for oil production that can be used for human consumption with concomitant production of high nutritive value of residues for ruminant feeds. The oil extraction technologies are available; however the high cost of ethanol and oil production should obtain high attention to make the technologies more applicable at farmers’ level. Key words: Crop by-products, energy, ethanol, residue, ruminant, feeds